Las tres Ces en la prevención de problemas legales en Cirugía Plástica, Estética y Reparadora: Comunicación, Consentimiento y Complicaciones. - VICENTE-RUIZ, Miriam; HONTANILLA, Bernardo (Cirugía Plástica Ibero-Latinoamericana)
Background and objective. The increasing demand for aesthetic procedures worldwide has been accompanied by a rise in legal claims against plastic surgeons in countries such as Spain, highlighting the need to implement effective strategies to prevent legal issues within our specialty. Methods. This study analyzed 199 judicial rulings in Spain related to plastic surgeries, both aesthetic and reconstructive, between 2018 and 2022, identifying the main causes behind these claims. Results. The most common factors in the lawsuits were found to be poor communication between surgeon and patient, inadequate informed consent, and unsatisfactory management of postoperative complications. Of the rulings analyzed, 41% resulted in a conviction, with lack of information and deficiencies in informed consent being the primary reasons for the judicial decisions. Conclusions. A set of practical recommendations is proposed to guide plastic surgeons in preventing legal problems, emphasizing the importance of improving communication, ensuring adequate informed consent, and proactively managing complications. Additionally, the importance of proper patient selection is highlighted, using tools such as the FATIMA acronym to identify those at higher risk of litigation. Finally, the authors warn about the risks associated with the use of simulation software and propose implementing the recording of consultations and surgeries to improve transparency and legal safety for patients and surgeons.